DEVELOPING TEAMWORK SKILLS IN PRIMARY SCHOOL STUDENTS - S. R. Qurbonov (Web of Journals Publishing, 2024)
This article explores effective methods aimed at developing teamwork skills in primary school students. Teamwork plays a crucial role in students' learning, social, and emotional growth. This study identifies key methods for effectively enhancing primary school students' teamwork abilities, including project-based learning, collaborative tasks, and role-playing. The results demonstrate that teamwork experiences are essential for social adaptability and improved academic outcomes in future learning processes.
Keywords: cooperative learning theory, social development theory, project-based learning, collaborative activities, role-playing, simulation.